Citizen Rights in Addressing Air Pollution and Ensuring a Healthy Environment: A Review - Nima Aali; Ramin Maleki (Journal of Advances in Environmental Health Research)
Air quality is one of the most vital elements for sustaining life on this planet. Without it, the existence of living beings would be impossible, making the preservation of air quality essential. However, the rapid growth of technology and urbanization has led to a significant increase in air pollutants. Given their harmful effects on human health and the environment, governments are compelled to adopt extraordinary measures to prevent air pollution and environmental degradation. Furthermore, a healthy and pollution-free environment is a fundamental citizenship right, as emphasized in numerous international and domestic laws. The persistent air pollution in Tehran, coupled with inadequate control and supervision, constitutes a violation of citizens’ rights. This review study explores the right of citizens to a healthy environment, with a focus on Tehran’s air pollution. It begins by examining Tehran’s air pollution from an environmental perspective. The second section discusses the legal framework in Iran, analyzing the rules, regulations, and approvals that address the right to a healthy living environment. Finally, the third section investigates civil rights to a healthy environment within international law, highlighting its recognition in both mandatory and non-mandatory documents.